Drift ebook The unmooring of american military power. - Maddow, Rachel (2012)
The #1 New York Times bestseller that charts America’s dangerous drift into a state of perpetual war. Written with bracing wit and intelligence, Rachel Maddow's Drift argues that we've drifted away from America's original ideals and become a nation weirdly at peace with perpetual war. To understand how we've arrived at such a dangerous place, Maddow takes us from the Vietnam War to today's war in Afghanistan, along the way exploring Reagan's radical presidency, the disturbing rise of executive authority, the gradual outsourcing of our war-making capabilities to private companies, the plummeting percentage of American families whose children fight our constant wars for us, and even the changing fortunes of G.I. Joe. Ultimately, she shows us just how much we stand to lose by allowing the scope of American military power to overpower our political discourse.  Sensible yet provocative, dead serious yet seriously funny, Drift  reinvigorates a "loud and jangly" political debate about our vast and confounding national security state.